Investigation of the role of sleep quality and sleep duration on fasting blood glucose level in acute ischemic stroke patients: A preliminary study - Putra, Riza P.; Islamiyah, Wardah R. (Narra J, 2021)
The aim of this study was to evaluate the association between the sleep quality and sleep duration with the level of fasting blood glucose in patients with acute ischemic stroke. A cross-sectional study was conducted among acute ischemic stroke patients admitted to Dr. Soetomo Hospital and Universitas Airlangga Hospital from May to October 2021. Patients who met the inclusion were enrolled. To assess the sleep quality, Pittsburgh Sleeps Quality Index (PSQI) was applied. To determine sleep duration during the nocturnal period, Fitbit Charge 2 HR device was used. Evaluation of plausible confounders was assessed through physical examination, interviews, and a set of validated questionnaires. A total of 30 acute ischemic stroke patients were included in this study. The mean age of the participants was 56.40±9.77 years and 60% were males. There were 63.3% patients classified as mild stroke and 36.7% moderate-severe stroke. The average PQSI score was 5.57±2.59, while the average sleep duration was 319.8±108.7 minutes. The average fasting blood glucose level was 89.03±14.71 mg/dL. Significant positive correlation was obtained between sleep duration and fasting blood glucose level (r=0.533; p=0.002). Similarly, there was no statistically significant correlation between sleep quality with the level of fasting blood glucose (r=-0.167; p=0.377). To the best of our knowledge, this is the first study assessing the correlation between sleep quality and sleep duration with the level of fasting blood glucose levels in patients with acute ischemic stroke. This study therefore might be of great interest to provide insights on the importance of sleep management in acute ischemic stroke patients.